Provocation as a partial defence in murder : a study on its applicability in relation to the battered women in Malaysia and the United Kingdom / Mimi Sintia Haji Mohd Bajury - Mohd Bajury, Mimi Sintia (Research Management Institute (RMI), 2008)
In criminal law, provocation is a possible defence by excuse or exculpation alleging a sudden or temporary loss of control (a permanent loss of control is in the realm of insanity) as a response to another's provocative conduct sufficient to justify an acquittal, a mitigated sentence or a conviction for a lesser charge. Provocation can be a relevant factor on a court's assessment of a defendant's mens rea, intention, or state of mind, at the time of an act of which the defendant is accused. This paper aims to examine the differences between the laws of provocation in Malaysia as compared to United Kingdom and to identify whether the Court in Malaysia will accept "battered women syndrome" as an element to qualify for the defence of provocation. In completing the paper, library based method is adopted to collect and analyse data gained from various sources. The major statute analysed in this paper is the Penal Code of Malaysia and the Homicide Act 1957 of the United Kingdom. A hypothesis of various decided cases by the courts in the United Kingdom involving battered women suffering from battered woman syndrome was done according to the law of provocation in Malaysia. This is to make an analogy of the outcome of those cases should they were decided in Malaysia. To date, evidence of battered woman syndrome had not been sought to be admitted in a local trial proceeding. It remains a big question mark whether it will be accepted by the court in Malaysia should such evidence is adduce during trial. It is proposed that the court in Malaysia should consider such evidence as to protect those wives who had been battered by their abusive husbands and still remained in the household due to several reasons, but one day decided to retaliate when they could not take it anymore. Therefore, it is hoped that this research paper could be a catalyst to some legal revolutions in protecting the "victim" who killed their abusive partner as a means of retaliation and self-defence when they could not tolerate further abuse.